The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3847/1538-3881/ab1d54
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming Rings in Lenticular Galaxies: Origin of the Gas

Abstract: Rings in S0s are enigmatic features which can however betray the evolutionary paths of particular galaxies. We have undertaken long-slit spectroscopy of five lenticular galaxies with UV-bright outer rings. The observations have been made with the Southern African Large Telescope (SALT) to reveal the kinematics, chemistry, and the ages of the stellar populations and the gas characteristics in the rings and surrounding disks. Four of the five rings are also bright in the Hα emission line, and the spectra of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…Molaeinezhad et al 2019). In Katkov et al (2014Katkov et al ( , 2015, Proshina et al (2019), andSil'chenko et al (2019), the authors discuss the origin of this counter-rotating gas and argue that S0s might accrete gas probably from filaments or from minor mergers. In parallel, numerous works have shown that S0s can be produced by galaxy mergers including major mergers (Bekki 1998;Querejeta et al 2015;Tapia et al 2017;Eliche-Moral et al 2018) as well as minor mergers (Bournaud et al 2005;Bekki & Couch 2011).…”
Section: Star-forming S0smentioning
confidence: 99%
“…Molaeinezhad et al 2019). In Katkov et al (2014Katkov et al ( , 2015, Proshina et al (2019), andSil'chenko et al (2019), the authors discuss the origin of this counter-rotating gas and argue that S0s might accrete gas probably from filaments or from minor mergers. In parallel, numerous works have shown that S0s can be produced by galaxy mergers including major mergers (Bekki 1998;Querejeta et al 2015;Tapia et al 2017;Eliche-Moral et al 2018) as well as minor mergers (Bournaud et al 2005;Bekki & Couch 2011).…”
Section: Star-forming S0smentioning
confidence: 99%
“…It is a rather low-luminosity S0 galaxy for which no SDSS data were found. We have made our own gri photometry which results are to be presented elsewhere (Proshina et al 2019); in the same paper we analyze also the long-slit kinematics. Here we note only a well-sampled ionized-gas velocity field ( Fig.…”
Section: Kinematicsmentioning
confidence: 99%
“…At least, starforming regions demonstrate quite recognizable emission-line spectra; and the models allow to determine the chemical composition -mainly oxygen abundances -by using the flux ratios of strong emission lines just for the case of the gas excited by young stars. We have checked the gas excitation in our S0 galaxies by studying the emission lines in the long-slit spectra obtained with the SCORPIO/BTA; for NGC 774 and NGC 3106 we have used the public spectral datacubes from the CALIFA survey (Sánchez et al 2016), for NGC 2697 and NGC 4324 -additional spectral data obtained earlier at the 11m SALT of the SAAO with the long-slit spectrograph RSS (Proshina et al 2019) have been involved into our present analysis. Weak and rather homogeneously distributed along the slit emission lines related to the gaseous disks with strongly decoupled rotation -those in NGC 2655, NGC 2787, NGC 3414, and NGC 7280, -have all demonstrated shock-like excitation: in their spectra the emission line [NII]λ6583 is comparable or even stronger than the Hα everywhere along the slit (see 2D spectra obtained along major axes of the mentioned galaxies in Fig.…”
Section: Gas Excitation and Metallicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approach is developed, for example, by Wu and Jiang [8]. Also there are another models which may explain the origin of outer stellar rings by the accretion of a cold gas from outside of the galaxy, e.g., see discussions in [9,10] and references therein.…”
Section: Introductionmentioning
confidence: 99%